Daratumumab–bortezomib–dexamethasone use in relapsed POEMS syndrome. Issue 3 (5th June 2022) - Khwaja, Jahanzaib; Keh, Ryan; Smyth, Duncan; Lunn, Michael Peter; D'Sa, Shirley; Sive, Jonathan
Abstract: POEMS syndrome is a rareparaneoplastic disorder driven by an underlying low level plasma cell dyscrasiaand associated with elevated serum vascular endothelial growth factor (VEGF). Dueto its rarity, there are no internationally agreed standards of care, with verylimited data to guide management in the relapse setting. Agents used in myelomaare rational choices and have been employed. Daratumumab has been reported intwo case studies with lenalidomide‐dexamethasone, one in the upfront and one inthe relapsed setting. We are the first to report here three cases ofdaratumumab‐bortezomib‐dexamethasone (DVd) use in relapsed POEMS postautologous stem cell transplant with good VEGF and clinical responses. Our casesadd to the literature on efficacy of daratumumab and are the first to report onits safe use with bortezomib in relapsed POEMS. It should be considered as aclinical option, in patients not responding to conventional first linetherapies.